Mao. 16 - Takahashi, Rumiko, 1957- (Shonen Sunday comics special., 2024)
"When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! Mao desperately tries to connect with his newly resurrected best friend, but the Goko clan has other plans for Daigo's zombie body. Then, the gang is tasked with finding a missing little girl. Their search leads them to a mysterious new curse clan led by a fire-wielding princess with an unscrupulous past and an evil agenda..." -- back cover